Detection of Efflux Pumps by mdeA gene, a Chromosomally-Encoded from Multidrug Staphylococcus aureus isolates - AL-Dahlaki, Shaymaa Majeed; Alwan, Shahad Saad (Journal of Neonatal Surgery, 2025)
Objective: Isolation and Identification of S.aureus and study their susceptibility, study mdeA gene, a Chromosomally-Encoded Multidrug Efflux Pump, from Staphylococcus aureus in patient of Baquba city. Materials and Methods: A total of 25 clinical specimens of Staphylococcus aureus isolates were collected from Baquba Teaching Hospital between June,1, 2022 to August,1, 2022. The isolates were identified based on their cultural characteristics, microscopic examination of cells, and biochemical tests. Antibiotic susceptibility testing was performed using an antibiotic diffusion disc assay to determine the sensitivity of the isolates to Staphylococcus aureus. The mdeA gene from S. aureus was also studied using the PCR technique. Results: The results show that the Staphylococcus aureus distributed as (4)(16%) samples from blood, 4(16%) samples from urinary tract infections, 6(24%) from wound infections , 2(8%) samples from burn infections, 3(12%) from ear swabs and 6(16%) samples from nasal swabs. The collected isolates were initially diagnosed in hospitals as Staphylococcus aureus that resistant to methicillin formed 100% ,The result revealed that MRSA isolates appeared completely resistant (100%) to Ceftazidime and Cefepime, the results showed that the resistance rate of MRSA isolate to Amikacin, Genetamicin and Kanamycin was 10\18(55.6%), 12\18 (66.6%)and 16 (88.9%)respectively and quinolone antibiotic such as Levofloxacin 14/18( 77.7%), Norfloxacin 12/18 (66.6%) , Ofloxacin 12/18( 66.6 %) ,Ciprofloxacin4/18(22.2%). The presence of the mdeA gene in the isolates was verified using uniplex PCR, which is considered the gold standard approach. A solitary band was detected at a specific molecular weight of 677 (bp). Our findings demonstrated that (16) MRSA isolates Thus, the prevalence of mdeA in patients of Baquba hospital was (88.8%). The remaining 2(12.2%) isolates were mdeA-negative. Staphylococcus aureus exhibits a significant level of resistance to quinolone antibiotics. Conclusion: This resistance is further enhanced by the presence of the model gene in the isolates, contributing to bacterial resistance against the antibiotics often used in our local area.